A preliminary study of cerebral blood flow, aging and dementia in people with Down syndrome. Issue 12 (30th September 2020) - Thalman, S.; Van Pelt, K. L.; Lin, A.‐L.; Johnson, N. F.; Jicha, G.; Caban‐Holt, A.; Robertson, W.; Lightner, D.; Powell, D.; Head, E.; Schmitt, F.
Abstract: Background: People with Down syndrome (DS) develop Alzheimer's disease (AD) at an earlier age of onset than those with sporadic AD. AD neuropathology is typically present in DS by 40 years of age with an onset of dementia approximately 10 years later. This early onset is due to the overexpression of amyloid precursor protein from the third copy of chromosome 21. Cerebrovascular neuropathology is thought to contribute in 40–60% of cases sporadic AD. However, the vascular contribution to dementia in people with DS has been relatively unexplored. We hypothesised that vascular perfusion is compromised in older adults with DS relative to younger individuals and is further exacerbated in those with dementia. Method: Cerebral blood flow (CBF) was measured using pulsed arterial spin labelling in 35 cognitively characterised adults with DS (26–65 years). DS participants were also compared with 15 control subjects without DS or dementia (26–65 years). Linear regression evaluated the difference in CBF across groups and diagnosis along with assessing the association between CBF and cognitive measures within the DS cohort. Results: Cerebral blood flow was significantly lower among DS participants with probable AD compared with controls ( P  = 0.02) and DS participants with no dementia ( P  = 0.01). Within the DS cohort, CBF was significantly associated with the Severe Impairment Battery (SIB) measure and the Dementia Questionnaire for People with Learning Disabilities (DLD) rating ( F 3, 25  = 5.13; P  = 0.007). Both the SIB ( β  = 0.74; t  = 2.71; P  = 0.01) and DLD ( β  = −0.96; t  = −3.87; P  < 0.001) indicated greater impairment as global CBF decreased. Age was significantly associated with CBF among participants with DS. There was a non‐linear effect of age, whereby CBF declined more rapidly after 45 years of age. Conclusions: This preliminary study of CBF in DS indicates that cerebrovascular pathology may be a significant contributor to dementia in DS. CBF was associated with diagnosis, cognition and age. Notably, CBF decreases at a greater rate after age 45 and may represent a significant prodromal event in AD progression.